Zur Sozialgeographie der Religionsgemeinschaften im Orient - Wirth, Eugen (ERDKUNDE, 1965)
In Lebanon und Syria the various religious groups are differentiated from each other not only through their customs and religious buildings but even more by many elements of the cultural landscape and their economic attitudes where a direct link with the particular religion can no longer be recognized. The Christians of the Levant have for many reasons for about a century been particularly receptive for European and Western influences. The areas of Christian settlement have in consequences been predominant centres for the spread of innovations. The on the whole more progressive attitude and greater wealth of the Christian communities derives less from their religious ethics and beliefs than from secular structural characteristics. Everywhere, however, where the Mohammedan population has come into similarly close contacts with Western ideas and institutions the cultural landscapes of the different religious groups have become also rather alike. All religious groups imitated particularly willingly such examples which provide a higher social prestige. This has been accelerating the spread of many innovations especially in those areas where the religious groups live relatively amicably with each other rather than in strict seclusion. In discussing the conditions of the Near East social geography and geography of religions cannot be treated separately as until recent times the religious groups were also close social groups. Thus even attempting an analysis of the forces which have been shaping the cultural landscape religious, historical, social, economic, psychological, political and probably also anthropological factors appear almost inextricably interwoven.